PENINGKATAN KEMAMPUAN TEKNIKPASSINGBAWAH BOLA VOLI MELALUI LATIHAN METODE DRILL SISWA KELAS VIII-2 SMP NEGERI 8 TEBING TINGGI - Simanjuntak, Rommel (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This purposes of this research is to improve learning result on physical education subjectÂ through exercise drill method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class VIII-2, Junior High School State 8 Tebing Tinggi which amounted to 40 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the exercise throughdrill method of physical education can improve learning result of under pass which characterized by increased mastery learning students, namely cycle I (77,5%), the cycleII(90%) and complete learn the clasical equal to 90 % in cycle II. Key Word :Exercise, Drill, Under pass